Zinner's Syndrome - Kuo, J. (Medknow Publications Pvt Ltd, 2011)
A 52-year-old male was subjected to an F-18 fluorodeoxyglucose positron emission tomography/computed tomography (FDG PET/CT) study for the evaluation of newly diagnosed non-Hodgkin's lymphoma. An incidental non-FDG avid urinary bladder mass was detected, as well as an absent kidney. Ureterocele was suspected, but subsequently a seminal vesicle cyst was confirmed on a CT urogram.